2014
DOI: 10.1155/2014/593121
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation of Fuel Cell Dynamics for Electrical Energy Usage of Hercules Airplanes

Abstract: Dynamics of proton exchange membrane fuel cells (PEMFC) with hydrogen storage system for generating part of Hercules airplanes electrical energy is presented. Feasibility of using fuel cell (FC) for this airplane is evaluated by means of simulations. Temperature change and dual layer capacity effect are considered in all simulations. Using a three-level 3-phase inverter, FC's output voltage is connected to the essential bus of the airplane. Moreover, it is possible to connect FC's output voltage to airplane DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The lumped parameter approach has been successfully used for the analysis of hybrid-electric propulsive architectures [13][14][15]. Other studies have dealt with the same approach to preliminarily design various components of all-electric propulsion systems which were separately sized with simplified models [16,17]. In [18] a propulsive architecture similar to that proposed in this study is analyzed focusing on the energy conversion and the control system: the types of DC/DC and DC/AC converters, including the technologies on which they are based, are evaluated to find the optimal solution for coupling the electric sources and the motor.…”
Section: State-of-the-artmentioning
confidence: 99%
“…The lumped parameter approach has been successfully used for the analysis of hybrid-electric propulsive architectures [13][14][15]. Other studies have dealt with the same approach to preliminarily design various components of all-electric propulsion systems which were separately sized with simplified models [16,17]. In [18] a propulsive architecture similar to that proposed in this study is analyzed focusing on the energy conversion and the control system: the types of DC/DC and DC/AC converters, including the technologies on which they are based, are evaluated to find the optimal solution for coupling the electric sources and the motor.…”
Section: State-of-the-artmentioning
confidence: 99%
“…A PID controller was used to regulate the output voltage at a certain set point via controlling the flow rate of hydrogen and oxygen for a hybrid power-plant system of a 240 W PEM fuel cell stack used for a C-130 Hercules aircraft, as reported by [24].…”
Section: Pid Controller For Air and Hydrogen Supplymentioning
confidence: 99%
“…Radmanesh et al [7] reported that storing hydrogen in the form of highly pressurised gas is the cheapest method, due to developments in composite materials that offer storing pressure up to 800 bar. However, pressurised hydrogen gas is usually stored in steel tanks with a pressure range between 200 and 300 bar.…”
Section: Introductionmentioning
confidence: 99%